Further revision of the mesh-web spider genus Taira Lehtinen, 1967 (Amaurobiidae), with the description of six new species - Zhao, Jing-Xia; Wang, Lu-Yu; Irfan, Muhammad; Zhang, Zhi-Sheng (Zootaxa, 2021)
The cribellate, Asian endemic, spider genus, Taira is further studied, and six new species are recognized and described from China and Eastern Malaysia (Borneo): Taira borneoensis sp. nov. (♀), Taira gyaisiensis sp. nov. (♀), Taira nyagqukaensis sp. nov. (♀), Taira wanzhouensis sp. nov. (♂♀), Taira xuanenensis sp. nov. (♂) and Taira yangi sp. nov. (♂♀). Males of Taira latilabiata Zhang, Zhu & Song, 2008 and Taira obtusa Zhang, Zhu & Song, 2008 are also described for the first time. Drawings of the copulatory organs of the six new species, and comparative photos of the habitus and copulatory organs of all described species are provided, except for the male palp of the type species, T. flavidorsalis (Yaginuma, 1964). New records of known species and distribution maps are presented.